Experimental study on shale fracturing assisted by low-temperature freezing (Fracture and Structural Integrity, 2018)
Under the cold impact of liquid nitrogen, the shale suffers from the significant freezing damage, which provides the possibility of liquid nitrogen fracturing. Moreover, shale fracturing assisted by liquid nitrogen can effectively reduce reservoir pollution. In this paper, the hydraulic fracturing experiments of natural shale samples frozen by liquid nitrogen were carried out to investigate the factors affecting the crack propagation of shale after low temperature fracturing. The results show that a large number of cracks or macropores form inside the natural shale sample after freezing treatment by liquid nitrogen. The fracture pressure of the shale decreases with increasing impact time at the beginning of the immersion time, and remains substantially stable after an immersion of 2 hours. When the freezing time increases, the crack initiation time increases accordingly. After low temperature impact, the fracture pressure of shale decreases with the increase of stress difference, but the cracking times vary with the stress with obvious regularity. It is easier to form main fracture with larger displacement on the premise of well-developed shale bedding.
Keywords: Liquid nitrogen; Freezing; Hydraulic fracture; Fracture pressure; Fracture initiation time